Flower-like three-dimensional bifunctional cathode catalyst for high-performance Li–O2 batteries: ZIF-67@3D-N/rGO. Issue 4 (15th February 2022) - Zhang, Yanjia; Xiao, Jie; Dong, Peng; Gu, Yang; Wu, Hongkun; Ding, Kai; Zeng, Xiaoyuan; Zhang, Yingjie
Abstract: To accelerate the practical application of Li–O2 batteries. A catalyst with outstanding oxygen reduction reaction and oxygen evolution reaction catalytic activity is required. Here, in-situ growth ZIF-67 within three-dimensional nitrogen-doped reduced graphene oxide (3D-N/rGO) layers was used to investigate a bifunctional catalyst. The inner space is supported by ZIF-67 particles, while 3D-N/rGO extends a suitable three-phase reaction interface and enhances O2 adsorbability. When assembled battery with normal electrolyte, it delivered a high specific capacity of 12028 mAh g −1, and stabilised for 203 cycles at 200 mA g −1 with a limited capacity of 500 mAh g −1 . When LiBr-gel polymer electrolyte (GPE) was used instead of electrolyte the lithium metal anode, the polarisation value of LiBr-GPE in Li/Li batteries was only about 0.0384 V after continuous working for 1600 h. When used as a cathode catalyst in Li–O2 batteries, the electrode performance was doubled compared with using the normal electrolyte. These findings pave the way for developing of all-encompassing battery materials with high capacity and long cycle life.